Studying disciplinary corpora to teach the craft of Discussion. (11th February 2016) - Cotos, Elena; Link, Stephanie; Huffman, Sarah
Abstract : Producing publishable quality research articles is a difficult task for novice scholarly writers. Particularly challenging is writing the Discussion/Conclusion section, which requires taking evaluative and interpretive stances on obtained results and substantiating claims regarding the worth of the scholarly contribution of the article to scientific knowledge. Conforming to the expectations of the target disciplinary community adds another dimension to the challenge. Corpus-based genre analysis can foster postgraduate writing instruction by providing insightful descriptions of rhetorical patterns and variation in disciplinary discourse. This paper introduces a pedagogically-oriented cross-disciplinary model of moves and steps devised through top-down corpus analysis. The model was applied to pedagogical materials and tasks designed to enhance genre and corpus-based teaching of Discussion/ Conclusions with an explicit focus on rhetorical conventions.